Nystagmus may be the first neurological sign in early stages of spinocerebellar ataxia type 3 - Gama, Maria Thereza Drumond; Rezende, Flávio Moura, Filho; Rezende, Thiago Junqueira Ribeiro; Braga, Pedro, Neto; França, Marcondes Cavalcante, Junior; Pedroso, José Luiz; Barsottini, Orlando Graziani Povoas (Arquivos de Neuro-Psiquiatria, 2021)
Background: Spinocerebellar ataxia type 3 (SCA3) is the most common autosomal dominant spinocerebellar ataxia worldwide. Almost all patients with SCA3 exhibit nystagmus and/or saccades impairment. Objective: To investigate the presence of nystagmus as an early neurological manifestation, before ataxia, in some patients with SCA3 in the first six months of the disease. Methods: We evaluated a series of 155 patients with clinically and molecularly proven SCA3 between 2013 and 2020. Data regarding sex, age, age at onset, disease duration, CAG repeat expansion length, first symptom, presence of ataxia, scores on SARA and ICARS scales, and presence and characteristics of nystagmus were collected. Results: We identified seven patients with symptomatic SCA3 who presented with isolated nystagmus. In these seven individuals the age at onset ranged from 24 to 57 years, and disease duration from four to six months. Conclusions: Our study showed that nystagmus may be the first neurological sign in SCA3. This clinical observation reinforces the idea that the neurodegenerative process in SCA3 patients may start in vestibular system connections or in flocculonodular lobe. This study adds relevant information about pre-symptomatic features in SCA3 that may work as basis for a better understanding of brain degeneration and for future therapeutic clinical trials.
Keywords: Machado-Joseph Disease; Ataxin-3; Neurodegenerative Diseases; Cerebellar Ataxia